The Role of Parental Psychological Resilience in Predicting Children's Emotional Competence in the Kingdom of Saudi Arabia - Al-Adsani, Lamia Abdullah (Journal of Posthumanism, 2025)
The current study aimed to investigate the relationship between parental psychological resilience and emotional competence in their children. It also aimed to reveal the significance of differences in parents' psychological resilience according to the variables of parents (father/mother), parental age, and the interaction between them. It also aimed to identify the possibility of predicting children's emotional competence through parents' psychological resilience. The study was conducted on a sample of 385 fathers and mothers, randomly selected. The study followed a descriptive, correlational, causal and comparative approach, using the Psychological Resilience Scale (prepared by van der Meer et al., 2018) and the Emotional Competence Scale (prepared by Nikčević-Milković, Jurković, & Jerković, 2020). A significant correlation exists between parental resilience and their children's emotional competence. There are significant differences in parental resilience according to the parental variables (father/mother), parental age, and the interaction between them, favouring mothers and younger age groups. The results also revealed the predictive power of parental resilience in detecting emotional competence in children. In light of the findings, the study recommended the importance of integrating the concepts of psychological resilience into the content of family and awareness programs offered by educational and community institutions, with special attention given to mothers to support their educational roles. It also recommended developing sustainable psychological support programs targeting the older age group of parents. Further qualitative research should also be conducted to explore the mediating variables that may contribute to explaining the relationship between parental resilience and children's emotional competence.